DESIGN AND ASSESSMENT OF BRAIN TRAINING GAME - CHEN, ZHENG HORNG (Universiti Teknologi PETRONAS, 2017)
Do brain games works? Brain games have been the attention of neuroscientists in these recent years. The market of brain training games has increased drastically, and every company claims that their games can train the users’ brain like memory, problem solving, reaction speed, etc. Yet, published research studies on brain games still cannot provide a strong evidence that these games benefit the brains. Thus, this project is to assess the effectiveness of existing brain games, specifically on memory aspect. 10 subjects were gathered and required to play a selected memory game. EEG data for each subject was collected before, during and after playing the game. A performance test was also conducted before and after playing game.